What unites us [large type] : reflections on patriotism - Rather, Dan; Kirschner, Elliot (Thorndike Press, a part of Gale, a Cengage Company, 2018)
At a moment of crisis over our national identity, journalist Dan Rather reflects on what it means to be an American. He reminds us of the principles upon which the United States was founded. Looking at the freedoms that define us, from the vote to the press; the values that have transformed us, from empathy to inclusion to service; the institutions that sustain us, such as public education; and the traits that helped form our young country, such as the audacity to take on daunting challenges in science and medicine, Rather brings to bear his decades of experience on the frontlines of the world's biggest stories. As a living witness to historical change, he offers up an intimate view of history, tracing where we have been in order to help us chart a way forward and heal our bitter divisions.